Overexpression of MdIAA9 confers high tolerance to osmotic stress in transgenic tobacco - Huang,Dong; Wang,Qian; Duan,Dingyue; Dong,Qinglong; Zhao,Shuang; Zhang,Maoxue; Jing,Guangquan; Liu,Changhai; Nocker,Steve van; Ma,Fengwang; Li,Chao (PeerJ, 2019)
Auxin is a plant hormone that takes part in a series of developmental and physiological processes. There are three major gene families that play a role in the early response of auxin and auxin/indole-3-acetic acid (Aux/IAA) is one of these. Although the genomic organization and function of Aux/IAA genes have been recognized in reference plants there have only been a few focused studies conducted with non-model crop plants, especially in the woody perennial species. We conducted a genomic census and expression analysis of Aux/IAA genes in the cultivated apple (Malus × domestica Borkh.). The Aux/IAA gene family of the apple genome was identified and analyzed in this study. Phylogenetic analysis showed that MdIAAs could be categorized into nine subfamilies and that these MdIAA proteins contained four whole or partially conserved domains of the MdIAA family. The spatio-specific expression profiles showed that most of the MdIAAs were preferentially expressed in specific tissues. Some of these genes were significantly induced by treatments with one or more abiotic stresses. The overexpression of MdIAA9 in tobacco (Nicotiana tabacum L.) plants significantly increased their tolerance to osmotic stresses. Our cumulative data supports the interactions between abiotic stresses and plant hormones and provides a theoretical basis for the mechanism of Aux/IAA and drought resistance in apples.
Keywords: Apple; Auxin; AUX/IAA gene family; Expression analysis; Abiotic stress